The increase in allergic conditions based on a review of literature - Gutowska-Ślesik, Joanna; Samoliński, Bolesław; Krzych-Fałta, Edyta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
The global interest in allergic disease epidemiology in the 20th and 21st centuries is a result of their growing prevalence of unprecedented, pandemic proportions. According to the 2011 White Book on Allergy, the prevalence of allergic conditions rises dramatically worldwide, both in developed and developing countries, with the rates of asthma ranging from 1% to 20%, allergic rhinitis from 1% to 18%, and skin allergies from 2% to 10% in various populations. The growing prevalence of allergies is particularly noticeable in children, who have been affected most by this trend for the last two decades.